How (5′S) and (5′R) 5′,8-Cyclo-2′-Deoxypurines Affect Base Excision Repair of Clustered DNA Damage in Nuclear Extracts of xrs5 Cells? A Biochemical Study - Boguszewska, Karolina; Szewczuk, Michał; Kaźmierczak-Barańska, Julia; Karwowski, Bolesław T. (Cells (Basel, Switzerland), 2021)
The clustered DNA lesions (CDLs) are a characteristic feature of ionizing radiation’s impact on the human genetic material. CDLs impair the efficiency of cellular repair machinery, especially base excision repair (BER). When CDLs contain a lesion repaired by BER (e.g., apurinic/apyrimidinic (AP) sites) and a bulkier 5′,8-cyclo-2′-deoxypurine (cdPu), which is not a substrate for BER, the repair efficiency of the first one may be affected. The cdPus’ influence on the efficiency of nuclear BER in xrs5 cells have been investigated using synthetic oligonucleotides with bi-stranded CDL (containing (5′S) 5′,8-cyclo-2′-deoxyadenosine (ScdA), (5′R) 5′,8-cyclo-2′-deoxyadenosine (RcdA), (5′S) 5′,8-cyclo-2′-deoxyguanosine (ScdG) or (5′R) 5′,8-cyclo-2′-deoxyguanosine (RcdG) in one strand and an AP site in the other strand at different interlesion distances). Here, for the first time, the impact of ScdG and RcdG was experimentally tested in the context of nuclear BER. This study shows that the presence of RcdA inhibits BER more than ScdA; however, ScdG decreases repair level more than RcdG. Moreover, AP sites located ≤10 base pairs to the cdPu on its 5′-end side were repaired less efficiently than AP sites located ≤10 base pairs on the 3′-end side of cdPu. The strand with an AP site placed opposite cdPu or one base in the 5′-end direction was not reconstituted for cdA nor cdG. CdPus affect the repair of the other lesion within the CDL. It may translate to a prolonged lifetime of unrepaired lesions leading to mutations and impaired cellular processes. Therefore, future research should focus on exploring this subject in more detail.